Chemical Control on Contamination Caused by Three Molds in Edible Mushroom Production - Yizhou Wang; Yiting Xie; Dengke Chao; Xiangying Xiao; Changhua Gu (BioResources)
This experiment aimed to test the effectiveness of four antifungal chemicals in controlling mold contamination in edible mushroom production. The antifungal chemicals were terbinafine hydrochloride, prochloraz, azoxystrobin, and sodium dichloroisocyanurate. The inhibitory effects of the chemicals were evaluated for inhibition on Cladosporium sp., Aspergillus niger, and Neurospora sp. The mycelia of the three molds and Morchella sextelata were cultured individually and co-cultured on plates with different concentrations of these chemicals, and then the mycelial growth was observed. By comparing the growth areas under the same conditions, the appropriate concentrations of each chemical were determined. The results indicated that terbinafine hydrochloride and prochloraz significantly inhibited the mycelial growth of all three mold species at certain concentrations, whereas their impact on the mycelial growth of M. sextelata was not significant. These results suggest that these two chemicals are effective in controlling the mycelial growth of the three molds, potentially increasing the yield and quality of M. sextelata and reducing mold contamination during storage and transportation.